Respuesta :
[tex]f(x) = -x^2 + 4[/tex]
[tex]g(x) = 6x[/tex]
[tex](g - f)(3) = 6(3) - (-(3)^2 + 4)[/tex]
[tex](g - f)(3) = 18 - (-9 + 4)[/tex]
[tex](g - f)(3) = 18 - (-5)[/tex]
[tex](g - f)(3) = 18 + 5[/tex]
[tex](g - f)(3) = 23[/tex]
[tex]g(x) = 6x[/tex]
[tex](g - f)(3) = 6(3) - (-(3)^2 + 4)[/tex]
[tex](g - f)(3) = 18 - (-9 + 4)[/tex]
[tex](g - f)(3) = 18 - (-5)[/tex]
[tex](g - f)(3) = 18 + 5[/tex]
[tex](g - f)(3) = 23[/tex]
f(x) = 4 - x² Df: x∈R
g(x) = 6x Dg: x∈R
Df = Dg therefore (g - f)(x) = g(x) - f(x)
(g - f)(3) = g(3) - f(3)
subtitute the value of x to equations:
g(3) = 6 · 3 = 18
f(3) = 4 - 3² = 4 - 9 = -5
(g - f)(3) = 18 - (-5) = 18 + 5 = 23
g(x) = 6x Dg: x∈R
Df = Dg therefore (g - f)(x) = g(x) - f(x)
(g - f)(3) = g(3) - f(3)
subtitute the value of x to equations:
g(3) = 6 · 3 = 18
f(3) = 4 - 3² = 4 - 9 = -5
(g - f)(3) = 18 - (-5) = 18 + 5 = 23